The Role of Consumer Characteristics and Marketing Mix on the Waste of Agricultural Products - M. Mahmoudi; H. Mohammadi; A. Karbasi (مجله اقتصاد و توسعه کشاورزی)
Introduction According to United Nations reports, the world population will increase from 7.2 billion people to 9.9 billion people during the years (2016-2050) with 38% growth. With population growth, amount of demand for food consumption (in order to eliminate malnutrition and demand caused by population growth) will increase by 150 to 170 percent by 2050. Today, one of the problems and threats facing the realization of food security in human societies is existence of an unusual amount of agricultural product waste. Every year, about one third and approximately 1.3 billion tons of total food production consumed by humans with a monetary value of 936 billion dollars, it is lost or wasted, which means that 0.9 million hectares and 306 square kilometers of water required for the production of agricultural products are wasted every year. The presence of this amount of waste in Iran's agricultural products indicates a significant waste of resources in country, and management of the country's resources (especially water) according to Iran's climatic situation and forecasting and drawing the future. It is telling that (resources used in agricultural sector) will soon become an important challenge. Considering that in country, 93.5% of water resources are used in agriculture, other issues such as pollution of water reserves, transfer of agricultural water to other sectors and low efficiency of water consumption in agriculture, increasing demand for water, increasing periods drought, phenomenon of fine dust, human impact on natural resources, etc. affect the amount of agricultural production. Subgroups of fruits and vegetables have the largest share in the consumption basket of households, but there are no specific statistics for recent years about share of consumption per capita of households (separated by products used) in Iran. It is important to note that the amount of waste generated by consumers varies between 1 kg per household per week and 4.5 kg per person per week, depending on consumer behavior. Given the significance of agricultural inputs, particularly water, in the production of these agricultural products and their substantial share in household consumption, this research focuses on the fruit and vegetable subgroups.